DYNAMICS OF HEALTH LAW CHANGE: A LEGAL AND SOCIAL ANALYSIS - Hotmaria Hertawaty Sijabat (Adisam Publisher, 2025)
This article analyses the dynamics of changes to the Health Law from a legal and social perspective, focusing on the triggering factors, implementation, and impact on society. Changes in health regulations are often influenced by technological developments, demographic changes, and demands for improved access and quality of health services. From a social perspective, public awareness of health rights and pressure from advocacy groups play an important role in shaping more inclusive regulations. While these changes aim to respond to complex health challenges, challenges such as resistance to change, implementation gaps, and potential conflicts of interest remain. Thus, transparent and collaborative measures are needed in the legislative process to ensure that changes to the Health Law are not only relevant, but also effective in achieving the expected social and legal goals.